Enhancing Students’ Motivation In English Learning Through Game-Based Puzzle Activities At SMPN 1 Pematangsiantar - Sinaga, Monika; Sihotang, Elina Rosa; Sebayang, Santa Nananda; Silalahi, Dumaris E. (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This qualitative descriptive study investigates the effectiveness of game-based puzzle activities in enhancing ninth-grade students’ motivation and comprehension of report text structure at SMPN 1 Pematangsiantar. Thirty-two students participated in a 30-minute timed group activity in which they assembled puzzle pieces (consisting of images, keywords, and fragmented descriptions related to a specific topic) and subsequently created a complete report text based on the assembled puzzle. Data were collected through participant observation, field notes, observation checklists, and semi-structured interviews, then analyzed using Miles and Huberman’s (1994) interactive model. The findings reveal that the puzzle assembly and text-creation process significantly increased students’ enthusiasm, collaboration, and confidence. Triangulation of data showed improvements in motivation indicators (up to 55% in enthusiasm and 40% in collaboration) and deeper understanding of report text elements, including general classification, description, and linguistic features such as simple present tense and general nouns. The activity successfully transformed the classroom into a lively, student-centered environment and promoted inclusivity, even among initially passive learners. This study concludes that game-based puzzle activities combining assembly and productive writing tasks are a practical, low-cost strategy to boost motivation and genre-based writing skills in EFL classrooms.